Based on knowledge capital value for disease cost accounting of diagnosis related groups - Duan, Jinli; Jiao, Feng; Xi, Jicheng; Zhang, Qichun (Frontiers in Public Health, 2024)
The National Health Commission and the other relevant departments in China have begun testing the Diagnosis Related Groups (DRGs) system in 30 pilot locations since 2019. In the process of DRG payment reform, accounting for the costs of diseases has become a highly challenging issue. The traditional method of disease accounting method overlooks the compensation for the knowledge capital value of medical personnel.The primary objective of this study is to analyze the cost accounting scheme of China's Diagnosis Related Groups (C-DRG), focusing on the value knowledge capital.The study initially proposes a measurement index system for the value of knowledge-based capital, including the difficulty of disease treatment, labor intensity of disease treatment, risk of disease treatment, and operation/treatment time for diseases.The Analytic Hierarchy Process (AHP) is then utilized to weight the features of medical workers' knowledge capital value. Firstly, pairwise comparisons are conducted in this stage to develop a two-pair judgment matrix of the primary indicators. Secondly, the eigenvectors corresponding to the maximum eigenvalues of the matrix are calculated to generate the weight coefficient of each feature. The consistency test is carried out after this stage. An empirical analysis is conducted by collecting data, including the full costs of treating three types of diseases-hip replacement, acute simple appendicitis, and heart bypass surgery-from one public medical institution.